Chromatographic method for determining 6‑mercaptopurine in skin permeation assays for assessing cutaneous exposure risk - Oliveira, Gabriel de Sousa (2025)
6-Mercaptopurine monohydrate (6-MP) is a drug often used in leukemia chemotherapy, but limited information is available about its cutaneous absorption, which raises concerns about occupational risks for healthcare professionals and caregivers. This study aimed to validate an analytical method using high-performance liquid chromatography (HPLC) for quantifying 6-MP in the skin, allowing the assessment of its cutaneous permeation. The validation of the proposed method demonstrated high selectivity against skin interferents, linearity (R = 0.999), precision, and sensitivity, with detection and quantification limits of 0.13 μg/mL and 0.39 μg/mL, respectively. The developed extraction procedure allowed reproducible drug recovery from the stratum corneum and remaining skin, minimizing the impact of enzymatic metabolism in these biological matrices. Using the developed method, a preliminary skin permeation test on porcine skin showed that 6-MP is retained mainly in the remaining skin, accumulating approximately 2% of the total dose applied within 30 min of testing, suggesting a high risk of dermal exposure. The results reinforce the need for preventive measures, such as personal protective equipment and strict handling protocols, to minimize drug exposure. Thus, the method described constitutes an essential tool in assessing the risk of topical contamination of 6-MP and can be used in long-term studies of skin permeation of this drug, contributing to the safety of health professionals, caregivers, and patients.